Handbook of energy engineering calculations - 4 0 16; 1921- , Hicks, Tyler Gregory; 5 (New York : McGraw-Hill, 2012)
Provides step-by-step procedures for performing hundreds of calculations related to applied energy engineering design and operating problems, with worked examples, focusing on greenhouse gas and carbon dioxide emissions control and energy conservation and reuse.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Mathematical models;Mathematical models -- Power (Mechanics);Force and energy;Engineering mathematics -- 20 -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Formulae;Handbooks, manuals, etc; 20; 2